(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
To evaluate in vitro anticancer activity on the MCF-7 cell line (Human breast cancer cell line) of Albizia saman (Leguminosae: family) flower extract. The monolayer cells were detached with trypsin-ethylene diamine tetra acetic acid (EDTA) to make single cell suspension and viable cells were counted using a hemocytometer. The cell suspension was diluted with medium containing 5% FBS (Fetal Blood Serum) to obtain final density of 1x105cells/ml. 100µl per well of cell suspension were seeded into 96-well plates at plating density of 10,000 cells/well and incubated to allow for cell attachment at 370C, 5% CO2, 95% air and 100% relative humidity. The results obtained from the in vitro studies performed using the human breast cancer cell line (MCF-7) reveals that the ethanolic extract of Albizia saman flower has a moderate anticancer activity with 94.72% growth inhibition at 200µg/ml. The IC50 value was 120.1µg/ml and the regression value was 0.999.